2007
DOI: 10.1016/j.livsci.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutrition on nitrogen, phosphorus, Cu and Zn in pig manure, and on emissions of ammonia and odours

Abstract: In order to reduce N, P and trace elements in pig manure, research toward a better agreement between supply and requirement has been undertaken in recent years, and ways to improve the biological availability of these elements in feedstuffs have been investigated. Substantial reduction in N excreted by pigs can be achieved by phase feeding combined with a better adjustment of the dietary amino acid balance. Feeding pigs with low N diets also allows a reduction of ammonia emission and to some extent the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 32 publications
1
56
0
3
Order By: Relevance
“…In pig production systems, faecal nitrogen (N) excretion, which amounts to 17% of the intake, consists of the undigested protein fraction and endogenous N losses, mainly digestive secretions and desquamation of intestinal cells. The remaining amino acids, after protein deposition and obligatory losses, are catabolized and excreted mainly as urea (Dourmad & Jondreville, 2007). In poultry litter (PL), crude protein (CP) content is about 20%, mainly as uric acid (Deshck et al, 1998), though Van Ryssen (2011) recorded broiler litter containing ca.…”
Section: Introductionmentioning
confidence: 99%
“…In pig production systems, faecal nitrogen (N) excretion, which amounts to 17% of the intake, consists of the undigested protein fraction and endogenous N losses, mainly digestive secretions and desquamation of intestinal cells. The remaining amino acids, after protein deposition and obligatory losses, are catabolized and excreted mainly as urea (Dourmad & Jondreville, 2007). In poultry litter (PL), crude protein (CP) content is about 20%, mainly as uric acid (Deshck et al, 1998), though Van Ryssen (2011) recorded broiler litter containing ca.…”
Section: Introductionmentioning
confidence: 99%
“…The need of pigs for the essential amino acids was widely studied and the researches confirm their inefficacity in satisfying the non-specific N requirements (Adkins et al, 1966;Allen and Baker, 1974;Featherstone, 1976); furthermore the essential amino acids must be supplied with the diet in certain amounts and proportions to obtain optimum efficiency of utilization of the proteins. Several authors report values of efficiency of dietary protein utilization between 18-40 % (de Lange et al, 1999;Della Casa, 2006;Dourmad et al, 1994;Monteiro et al, 2010;Mordenti et al, 1995, Rossi et al, 2005; according to Dourmad et al 2007, in pigs fed diets based on cereals and soybean flour during breeding-fattening, the N retention is of about 32%. The different protein utilization depends on several factors: composition of the diet, physiological state, growth intensity of the animals, breed and genotype, sex and slaughter weight (Bittante et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…According to this principle, and as reviewed by DOURMAD & JONDREVILLE (2007), reducing the dietary CP while balancing the diet with feed-use (FU) AA is an effective way of reducing N excretion, as long as pig performance and carcass composition are not adversely affected. These authors reported about 9% reduction in N excretion by growingfinishing pigs per percentage unit of CP reduction, when the dietary CP level was reduced from 178 to 136g kg -1 , without affecting energy efficiency, carcass lean percentage or average daily gain.…”
Section: Nutritional Strategies As a Tool For Sustainable Pork Producmentioning
confidence: 99%